Serum osteocalcin is associated with subjective stress in people with depression and type 2 diabetes. (December 2020) - Nguyen, Michelle M.; Anita, Natasha Z.; Darwish, Lina; Major-Orfao, Chelsi; Colby-Milley, Jessica; Wong, Sophie K.; Sugamori, Kim S.; Lanctôt, Krista L.; Herrmann, Nathan; Oh, Paul I.; Yang, Pearl; Shah, Baiju R.; et al.
Highlights: Osteocalcin (OCN) is a bone-derived mediator impaired in type 2 diabetes (T2DM). Higher serum carboxylated OCN was linked to perceived chronic stress in T2DM. OCN was particularly associated with perceived stress during depressive episodes. OCN may relate neuroendocrine stress susceptibility to depression pathophysiology. Abstract: Background: Low serum osteocalcin is a risk factor for type 2 diabetes mellitus (T2DM), and osteocalcin release from bone is associated with an acute stress response in mice. Both diabetes and stress are associated with depression. Here, we assess relationships between serum osteocalcin, depression and subjective stress in people with T2DM. Methods: Participants with T2DM (HbA1c above 6.4 %, impaired fasting glucose or impaired glucose tolerance) were assessed for a major depressive episode using the research version of the Structured Clinical Interview for DSM-5 depression criteria (SCID-5RV). Subjective stress over the past month was assessed using the Perceived Stress Scale (PSS). Serum carboxylated (cOCN) and fully decarboxylated (dcOCN) osteocalcin were assayed from fasting morning blood by commercial enzyme-linked immunosorbent assay. Results: Among 95 participants (mean age 62.4 ± 9.9, 51 % women), 22 % were experiencing a depressive episode (9 men, 12 women). The presence of a depressive episode was not associated with dcOCN or cOCN concentrations; however, higher concentrations of cOCN were associated with higher PSS scores in participants with depression (r = 0.585, p = 0.005). In an analysis of covariance model controlling for age, sex, body mass index, glycemic control (glycosylated hemoglobin), insulin resistance (homeostatic model), depression, and antidepressant use, cOCN was associated with PSS scores (F=10.302, p = 0.002), and this relationship was stronger in those with depression (depression × cOCN interaction F=4.978, p = 0.028). Although associations between dcOCN concentrations and PSS scores did not reach significance, the same trend seen with cOCN concentrations was observed in participants with depression for dcOCN (r=0.365, p=0.10), and for a depression × dcOCN interaction associated with PSS scores in the whole group (F=2.165, p = 0.15). Conclusions: Osteocalcin is a neuroendocrine marker associated with perceived chronic stress among people with T2DM experiencing a depressive episode.